High-purity copper electrolytic refining method and equipment
By using mesh interlayer to fix tantalum powder in the electrolytic cell of the high-purity copper electrolytic refining device to adsorb the anode mud in the electrolyte, the problem of filtration in the existing equipment is solved, the purity and production efficiency of copper are significantly improved, and the reusable tantalum powder is realized.
Patent Information
- Application Number
- CN202411912098.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
AI Technical Summary
The existing high-purity copper electrolytic refining equipment has poor controllability, and the circulation flow rate and purification cycle are unstable, which makes it difficult to effectively remove impurities in the electrolyte, affecting the purity of copper.
The electrolytic cell is equipped with a mesh interlayer, and the tantalum powder is fixed in the interlayer, and the anode mud in the electrolyte is adsorbed with the fluidity of the tantalum powder and a high specific surface area to prevent it from reaching the cathode, thereby purifying the electrolyte and improving the purity of the copper.
The anode mud is adsorbed by tantalum powder, which significantly reduces the particle size in the electrolyte, improves the purification effect of the electrolyte, enhances the purity of the cathode copper, and improves the production efficiency of high-purity copper. In addition, the tantalum powder can be reused by dilute nitric acid.
Smart Images

Figure CN119685885A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of structural assemblies of electrolytic cells, and in particular relates to a high-purity copper electrolytic refining device. Background Art
[0002] High-purity copper, as an extremely pure copper material, ensures its unique physical properties. Its properties make high-purity copper widely used in high-tech fields such as electronics, electrical, chemical, automotive, aerospace and new energy. The electrolytic refining technology for preparing high-purity copper is to use crude copper as the anode, titanium sheet as the cathode, and copper sulfate solution as the electrolyte to conduct electrolysis experiments. During the electrolysis process, the crude copper at the anode undergoes a dissolution reaction, and copper ions (Cu 2+ ) enters the solution, and under the action of the electric field, copper ions (Cu 2+ ) migrates to the cathode, where it obtains electrons and precipitates copper that is deposited on the cathode plate. The crude copper can be purified by electrolytic refining. However, the existing electrolytic refining equipment filters are mostly designed as external devices. The controllability of such circulating filtration devices is poor, and there is still instability in terms of circulation flow rate and purification cycle. The present invention aims to provide a new type of high-purity copper electrolytic refining device to solve these problems. Summary of the invention
[0003] In view of the problems existing in the background technology, the present invention provides a high-purity copper electrolytic refining device. By adding a sandwich layer for placing powder in the tank, tantalum powder is fixed in the sandwich layer, and the powder is controlled to be fully in contact with the electrolyte while not randomly dispersed into the electrolyte. When the electrolysis reaches a certain level, the generated anode mud (Cu (alkaline arsenate form), Pb (PbSO4), Bi [Bi (OH) 3] precipitation, Sb) will be suspended in the electrolyte, thereby achieving the purpose of purifying the electrolyte. At the same time, due to a part of the anode mud flowing to the cathode, the tantalum powder is fixed in the sandwich layer, and the powder is controlled to be fully in contact with the electrolyte. The mud will be adsorbed by the tantalum powder and will not reach the cathode, and further the purpose of electrolysis can be achieved to prepare cathode copper with higher purity. The technical solution includes: a power supply, an anode, a mesh interlayer for placing powder, tantalum powder, a cathode, an electrolytic cell and an electrolyte, wherein the anode and the cathode are respectively arranged on both sides of the electrolytic cell, and an inter-electrode distance is provided between the anode and the cathode; the electrolytic cell is filled with electrolyte; the anode and the cathode are respectively connected to the two poles of the power supply, and a mesh interlayer is installed in the electrolytic cell, the mesh interlayer is arranged between the anode and the cathode, and the tantalum powder is placed in the mesh interlayer.
[0004] The mesh interlayer is made of a mesh material with a pore size smaller than the particle size of the tantalum powder, and the mesh interlayer is not in contact with the anode and the cathode.
[0005] The tantalum powder includes: a first type of tantalum powder, a second type of tantalum powder, or a mixture of the first type of tantalum powder and the second type of tantalum powder;
[0006] The first type of tantalum powder has a grade of FTW60, a bulk density of 1.9 to 2.5 g / cc, and a Fischer-Tropsch particle size of 4.5 to 7.5 μm;
[0007] The grade of the second type of tantalum powder is FTW701, the bulk density is 1.5-2.0 g / cc, and the Fisher particle size is 3.5-5.5 μm.
[0008] The tantalum powder includes: a third type of tantalum powder, a fourth type of tantalum powder, or a mixture of the third type of tantalum powder and the fourth type of tantalum powder;
[0009] The third type of tantalum powder has a grade of FTD15, a bulk density of 4.5 to 6.5 g / cc, and a Fisher particle size of 12.0 to 18.0 μm;
[0010] The fourth type of tantalum powder has a grade of FTW20, a bulk density of 4.5-6.5 g / cc, and a Fisher particle size of 9.0-15.0 μm.
[0011] The tantalum powder is used to remove anode mud on the surface by using dilute nitric acid.
[0012] The anode is crude copper, the cathode is a titanium sheet, and the inter-electrode distance is 50-70 mm.
[0013] The beneficial effects of the present invention are:
[0014] 1. The present invention adds an interlayer in which tantalum powder can be placed in the electrolytic cell, and uses tantalum powder to achieve adsorption of suspended anode mud, so as to prevent the anode mud from contacting the cathode; specifically, by utilizing the good fluidity and high specific surface area of tantalum powder itself, the anode mud suspended in the electrolyte is adsorbed, which can effectively reduce the particle size in the electrolyte and purify the electrolyte. Compared with the traditional filtering method of the external device, this filtering evolution method improves the efficiency of electrolytic preparation of high-purity copper.
[0015] 2. Compared with the traditional method, the content of key impurity elements (Ag, Pb, Fe, Bi, Se, Te) in the cathode copper prepared by the present invention by adding tantalum powder is significantly reduced. In particular, tantalum powder has a significant effect on the content of Ag in the electrolyte. + It has obvious removal effect.
[0016] 3. Tantalum powder can be reused by removing the anode mud on the surface of tantalum powder after electrolysis using dilute nitric acid. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic structural diagram of a broad embodiment of a high-purity copper electrolytic refining device of the present invention.
[0018] Figure 2 The figure is a schematic diagram of a flow chart of an embodiment of the present invention during electrolytic refining.
[0019] Figure 3 It is a comparison chart of the number of particles in the electrolyte after the electrolysis process of Example 1 of the present invention and Comparative Example 1.
[0020] Figure 4 It is a comparison chart of the number of particles in the electrolyte after the electrolysis process of Example 1 and Example 2 of the present invention.
[0021] Among them, 1 is power supply, 2 is anode plate, 3 is mesh interlayer, 4 is tantalum powder, 5 is cathode plate, 6 is electrolytic cell, and 7 is electrolyte. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below in conjunction with the accompanying drawings.
[0023] like Figure 1 The broad embodiment of the present invention shown comprises: a direct current power source 1, an anode plate 2, a mesh interlayer 3 for placing tantalum powder, tantalum powder 4, a cathode plate 5, an electrolytic cell 6 and an electrolyte 7, wherein the anode plate 2 and the cathode plate 5 are respectively arranged on both sides of the electrolytic cell 6, and an inter-electrode distance is provided between the anode plate 2 and the cathode plate 5; a rectangular space is formed inside the electrolytic cell 6, the electrolytic cell 6 is filled with the electrolyte 7, and the anode plate 2 and the cathode plate 5 are respectively connected to the two poles of the power source 1;
[0024] A mesh interlayer 3 is installed in the electrolytic cell, and the mesh interlayer 3 is arranged between the anode plate 2 and the cathode plate 5, and the mesh interlayer 3 is not in contact with the anode plate 2 and the cathode plate 5, so as not to affect the electrolysis process; the tantalum powder is placed in the mesh interlayer 3, and the mesh interlayer 3 is made of a mesh material, ensuring that the pore size of the mesh is smaller than the particle size of the tantalum powder, so that the powder is fully in contact with the electrolyte, and the powder is not randomly dispersed in the electrolyte;
[0025] In this embodiment, crude copper is used as the anode plate and titanium sheet is used as the cathode plate. The shapes of the anode plate and the cathode plate are not necessarily plate-shaped, depending on the specific process. The inter-electrode spacing is 50-70 mm.
[0026] In this embodiment, tantalum powder 4 with good fluidity and high specific surface area is selected; specifically, the following four types of tantalum powder are used: the grade of tantalum powder of type 1 is FTW60, the bulk density (SBD) is 1.9-2.5 g / cc, and the Fisher particle size (Fsss) is 4.5-7.5 μm; the grade of tantalum powder of type 2 is FTW701, the bulk density (SBD) is 1.5-2.0 g / cc, and the Fisher particle size (Fsss) is 3.5-5.5 μm; the grade of tantalum powder of type 3 is FTD15, the bulk density (SBD) is 4.5-6.5 g / cc, and the Fisher particle size (Fsss) is 12.0-18.0 μm; the grade of tantalum powder of type 4 is FTW20, the bulk density (SBD) is 4.5-6.5 g / cc, and the Fisher particle size (Fsss) is 9.0-15.0 μm.
[0027] During electrolysis, the tantalum powder placed in the interlayer with mesh is one of the following schemes: 1. Tantalum powders of type 1 and type 2 of the four types above are mixed and placed in the interlayer with mesh; 2. Tantalum powders of type 3 and type 4 of the four types above are mixed and placed in the interlayer with mesh, so that the electrolyte contacts the tantalum powder in the interlayer with mesh; due to its good fluidity and high specific surface area, the tantalum powder absorbs the anode mud suspended in the electrolyte, thereby extending the use time of the electrolyte; at the same time, it effectively blocks the suspended anode mud from flowing to the cathode, realizes the purification of the electrolyte in the cathode area, thereby ensuring the purity of the final product and improving the production efficiency of high-purity copper;
[0028] In this embodiment, the operation process of electrolytic refining is as follows Figure 2 As shown, firstly, the prepared electrolyte is injected into the electrolytic cell, and cathode plates and anode plates are arranged on both sides of the electrolytic cell, and a certain inter-electrode distance is maintained according to the design; then, a mesh interlayer is arranged between the cathode plate and the anode plate, and then tantalum powder is placed in the mesh interlayer, and the preparation work is completed.
[0029] Then connect the power supply to the anode and cathode plates and start the power supply to carry out the electrolysis reaction.
[0030] During the electrolytic refining process, copper dissolution reaction occurs on the anode plate, causing the copper ions at the anode to gradually increase. Due to the action of the electric field, the copper near the anode will pass through the mesh interlayer to the cathode, where a copper precipitation reaction occurs to obtain high-purity cathode copper.
[0031] After the electrolysis is completed, the tantalum powder in the mesh interlayer is removed and the anode mud on the surface is removed using dilute nitric acid. The tantalum powder after acid washing (specifically using dilute nitric acid) to remove the anode mud on the surface of the electrolyzed tantalum powder can be reused.
[0032] Example 1
[0033] Place 4N electrolytic copper and titanium sheet on the left and right sides of the electrolytic cell, keep the inter-electrode distance at about 70mm, inject the pre-prepared electrolyte mother solution into the electrolytic cell (the initial electrolyte is a mixed solution containing 35ml / L nitric acid and 50g / L copper nitrate), and keep the liquid level at 2\3 to 3\4 of the electrolytic cell. Put tantalum powder (a mixture of FTW60 and FTW701) into the mesh interlayer in the electrolytic cell to ensure that it will not disperse into the electrolyte, start the DC power supply, and set it to 150A / m 2 The electrolysis time is 24 hours. When the electrolysis reaches a certain level, anode mud suspended in the electrolyte will be produced. The tantalum powder in the porous interlayer adsorbs the suspended anode mud and filters and purifies the electrolyte. When the copper precipitation reaches a certain level, the electrolysis process is stopped and the DC power supply is turned off. Take the electrolyte at this time and use the KD-4T particle counter to test the number of particles in the electrolyte.
[0034] Comparative Example 1:
[0035] The electrolytic preparation process and the formula of the electrolytic mother solution are the same as those in Example 1, except that no tantalum powder is added to the electrolytic cell. As in Example 1, the electrolyte is taken at the end of the electrolysis to test the number of particles.
[0036] Table 1 Comparison of the number of particles in the electrolyte of Example 1 and Comparative Example 1
[0037]
[0038] As shown in Table 1, it can be seen that the addition of tantalum powder has an adsorption effect on particles with smaller particle sizes. The number of particles with a size of 0.5-0.8μm has been reduced several times, and the number of particles with a particle size below 2μm has also been significantly reduced. Figure 3 As shown in the figure, the change process of the number of particles with different particle sizes can be seen. Therefore, compared with the electrolytic device without tantalum powder filtration, the adsorption and purification effect of the electrolytic device with tantalum powder added is obvious.
[0039] Embodiment 2:
[0040] Place 4N electrolytic copper and titanium sheet on the left and right sides of the electrolytic cell, keep the inter-electrode distance at about 70mm, inject the pre-prepared electrolyte mother solution into the electrolytic cell (the initial electrolyte is a mixed solution containing 35ml / L nitric acid and 50g / L copper nitrate), and keep the liquid level at 2\3 to 3\4 of the electrolytic cell. Put tantalum powder (a mixture of FTD15 and FTW20) into the mesh interlayer in the electrolytic cell to ensure that it will not disperse into the electrolyte, start the DC power supply, and set it to 150A / m 2. The electrolysis time is 24 hours. When the electrolysis reaches a certain level, anode mud suspended in the electrolyte will be produced. The tantalum powder in the porous interlayer adsorbs the suspended anode mud and filters and purifies the electrolyte. When the copper precipitation reaches a certain level, the electrolysis process is stopped and the DC power supply is turned off. Take the electrolyte at this time and use the KD-4T particle counter to test the number of particles in the electrolyte. The number of particles in the two different types of tantalum powder electrolytes of Example 1 and Example 2 is compared, and the results are shown in Tables 2 and Figure 4 It can be seen that the number of particles with a particle size of less than 0.8 μm in Example 1 is reduced by 1 times compared with that in Example 2. Therefore, the tantalum powder in Example 1 has good fluidity and high specific surface area, and has a better adsorption effect on the suspended anode mud in the electrolyte.
[0041] Table 2 Comparison of the number of particles in the electrolyte after filtering different types of tantalum powder in Example 1 and Example 2
[0042]
[0043] Embodiment 3:
[0044] Place 4N electrolytic copper and titanium sheet on the left and right sides of the electrolytic cell, keep the inter-electrode distance at 70mm, inject the pre-prepared electrolyte mother solution into the electrolytic cell (the initial electrolyte is a mixed solution containing 35ml / L nitric acid and 50g / L copper nitrate), and keep the liquid level at 2\3 to 3\4 of the electrolytic cell. Put tantalum powder into the mesh interlayer in the electrolytic cell to ensure that it will not disperse into the electrolyte, start the DC power supply, and set it to 150A / m 2 . The electrolysis time is 24 hours. Carefully peel off the precipitated copper from the titanium cathode plate to avoid damaging its surface. Perform a preliminary rinse to remove the electrolyte and impurities attached to the surface. Use deionized water for thorough cleaning to ensure the purity of the precipitated copper surface. Ultrasonicate the cleaned copper plate, place the copper plate in a container and add ethanol. The amount of ethanol is controlled to just immerse the copper plate to avoid contact with air during the ultrasonic process to oxidize the copper plate. Place the container in an ultrasonic cleaner for 5 minutes, and then take out the cathode plate and blow dry it to obtain a dry cathode copper plate for use.
[0045] Comparative Example 2:
[0046] The electrolysis process and the electrolysis mother solution formula are the same as those in Example 3, except that no tantalum powder is added.
[0047] The Ag content in the electrolyte of Example 3 and Comparative Example 2 is compared, and the results are shown in Table 3 below; the Ag content is reduced by 94%, which shows that the addition of surface tantalum powder has a significant effect on the Ag content in the electrolyte. +It has a certain removal effect, which is beneficial to the production of high-purity cathode copper; the key impurity elements (Ag, Pb, Se, Te, Bi, Fe) in the high-purity cathode copper plates prepared in Example 3 and Comparative Example 2 are compared, and the results are shown in Table 4. It can be seen that the content of Ag element in the high-purity copper sample prepared by electrolysis in Example 3 decreases from 9.3ppm to 2.3ppm, and Fe decreases from 5.1ppm to 0.001ppm, and the other key impurity elements all decrease significantly.
[0048] Table 3 Comparison of Ag content in the electrolyte of Example 3 and Comparative Example 2
[0049]
[0050] Table 4 Comparison of the contents of key impurity elements in the electrolyte of Example 3 and Comparative Example 2
[0051]
Claims
1. A high-purity copper electrolytic refining device, characterized in that: include: A power source (1), an anode, a mesh interlayer (3), tantalum powder (4), a cathode, an electrolytic cell (6) and an electrolyte (7), wherein the anode and the cathode are respectively arranged on both sides of the electrolytic cell (6), and an inter-electrode distance is provided between the anode and the cathode; the electrolytic cell (6) is filled with the electrolyte (7); the anode and the cathode are respectively connected to two poles of the power source (1); a mesh interlayer (3) is installed in the electrolytic cell, the mesh interlayer (3) is arranged between the anode and the cathode, and the tantalum powder is placed in the mesh interlayer (3).
2. A high-purity copper electrolytic refining device according to claim 1, characterized in that: The mesh interlayer (3) is made of a mesh material with a pore size smaller than the particle size of the tantalum powder, and the mesh interlayer (3) is not in contact with the anode and the cathode.
3. A high-purity copper electrolytic refining device according to claim 1, characterized in that: The tantalum powder (4) comprises: a first type of tantalum powder, a second type of tantalum powder, or a mixture of the first type of tantalum powder and the second type of tantalum powder; The first type of tantalum powder has a grade of FTW60, a bulk density of 1.9 to 2.5 g / cc, and a Fischer-Tropsch particle size of 4.5 to 7.5 μm; The grade of the second type of tantalum powder is FTW701, the bulk density is 1.5-2.0 g / cc, and the Fisher particle size is 3.5-5.5 μm.
4. A high-purity copper electrolytic refining device according to claim 1, characterized in that: The tantalum powder (4) comprises: a third type of tantalum powder, a fourth type of tantalum powder, or a mixture of the third type of tantalum powder and the fourth type of tantalum powder; The third type of tantalum powder has a grade of FTD15, a bulk density of 4.5 to 6.5 g / cc, and a Fisher particle size of 12.0 to 18.0 μm; The fourth type of tantalum powder has a grade of FTW20, a bulk density of 4.5-6.5 g / cc, and a Fisher particle size of 9.0-15.0 μm.
5. A high-purity copper electrolytic refining device according to claim 3 or 4, characterized in that: The tantalum powder (4) is used to remove anode mud on the surface using dilute nitric acid.
6. A high-purity copper electrolytic refining device according to claim 1, characterized in that: The anode is crude copper, the cathode is a titanium sheet, and the inter-electrode distance is 50-70 mm.
Citation Information
Cited By
Assistant composition and method for preparing high-purity copper through electrolysis
CN121046902A